DESCRIPTION OF SANDY AREAS OF FERGANA VALLEY (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article provides a general description of the sandy areas located in the southwestern part of the Fergana Valley. Geomorphological features, climatic conditions and biological diversity of sandy areas were studied. Also, ecological problems arising as a result of anthropogenic effects are considered. The results of the research show that it is necessary to take the necessary measures in the sustainable management of sandy areas, to strengthen environmental monitoring and to fight against soil erosion. Maintaining the natural balance of these areas is ecologically and economically important